Consumers' responses to health claims in the context of other on-pack nutrition information: A systematic review - Talati, Zenobia; Pettigrew, Simone; Neal, B.; Dixon, H.; Hughes, C.; Kelly, B.; Miller, C. (2017)
Context: The presence of health claims on food packaging can positively bias consumers' evaluations of foods. Objective: This review examined whether cognitive biases endure when other sources of nutrition information [the nutrition facts panel (NFP) and front-of-pack labels] appear on-pack with health claims. Data sources: The following databases were searched: Web of Science, Ovid, Google Scholar, ScienceDirect, Scopus, ProQuest, and Wiley Online Library. Study selection: The search terms ("health claim*" OR "nutri* claim") AND ("food label*" OR "front of pack") were used to identify studies. Data extraction: Twenty-four studies that examined health claims and front-of-pack labels or the NFP were included. Results: The NFP can reduce bias, but only if consumers view it and interpret it correctly, which often does not occur. Front-of-pack labels show greater promise in reducing bias created by health claims. Conclusions: These findings are relevant to policymakers who are considering the effectiveness of mandating an NFP and/or a frontof- pack label alongside health claims.